Position statement of the Polish Society of Gastroenterology and the National Gastroenterology Consultant on vaccination against COVID-19 among patients with inflammatory bowel diseases - Piotr Eder; Michał Łodyga; Agnieszka Dobrowolska; Jarosław Reguła; Grażyna Rydzewska (Gastroenterology Review)
The COVID-19 (coronavirus disease 2019) pandemic significantly impacted the functioning of the whole world, both with regard to health, society, and economics. It is the greatest civilizational challenge for humanity since World War II. So far, more than 80 million SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2) infections have been reported, and nearly 2 million people have died from this infectious disease (as of 4.01.2021) [1]. However, accurate statistics on the number of patients in whom infection did not lead to death but caused significant organ complications are unknown. The long-term effects of infection with the new coronavirus species also remain unelucidated.